Influence of User Characteristics on the Utilisation of Electronic Resources in a Nigerian University Library - Aniedu, O. N.; Uzuegbu, C. P. (MiddleBelt Journal of Library and Information Science, 2014)
The study sought to identify the influence of user characteristics on utilization of Abia State University E-library by undergraduate students. The survey research design was adopted. The YaroYammane (1969) statistical formula was employed to select a sample of 382 out of 6,500 students that comprised the total study population. Questionnaire was the instrument for data collection. The instrument was validated by experts in the library and information science profession, administered by hand and analyzed with statistical charts and tables. The findings of the research include that age, skill, personal attribute and environment has a positive influence on the use of e-library while gender, the sex of the user, has no influence on the use of e-library.